Integration of trees and livestock in tropical agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Although trees and livestock are not closely-linked components of modem western agricultural systems, this was not always the case. Traditional 'woodpasture' systems were widespread in Europe and allowed production of meat, firewood and building...